Pengaturan Hukum Tentang Sertifikasi Halal Dalam Bisnis Kuliner Frozen Food Di Kota Matara - A'yuni, Qurratu; Kurniawan (Commerce Law, 2024)
This research aims to determine the role of the Institute for the Study of Food, Drugs, and Cosmetics Indonesian Council of Ulama (LPPOM MUI) in supervising and enforcing regulations related to halal certification in the frozen food culinary business in Mataram City and to find out how Halal Product Guarantee Organizing Agency (BPJPH) and LPPOM MUI can increase the effectiveness of supervision and law enforcement related to regulating halal certification in the frozen food culinary business in Mataram City. The type of research used in this research is Normative-Empirical Legal Research, using a statutory approach, a conceptual approach, and a sociological approach. From the results of the research and discussion, it can be concluded that there are two roles of LPPOM MUI, namely as a guardian of the halal quality of frozen food products and as an examiner or tester of the halal quality of frozen food products. Meanwhile, the way for BPJPH and LPPOM MUI to increase the effectiveness of supervision and law enforcement related to regulating halal certification in the frozen food culinary business in Mataram City is by strengthening cooperation between BPJPH and LPPOM MUI, strengthening information technology, strict sanctions, and involving community involvement.